DB2® Universal Database for OS/390® Version 7.1 Certification Guide - Yevich, Richard; Lawson, Susan (Pearson, 2001)
IBM's definitive, authoritative DB2 for OS/390 and z/OS reference and self-study guide! The only comprehensive IBM(r) DB2 UDB V7.1 for OS/390 certification prep guide Covers administration, security, SQL, application development, tuning, and much more Contains dozens of expert DB2 tips, techniques and guidelines CD-ROM contains complete DB2 for OS/390 sample exam Written by IBM Gold Consultants for DB2 and S/390 The total resource for every professional running DB2 UDB V7.1 in OS/390 and z/OS environments Database administration, security, monitoring, tuning, SQL, and application development Sample test questions help you prepare for IBM's new DB2 UDB V7.1 for OS/390 exams The CD-ROM included with this book contains a complete IBM DB2 for OS/390 certification sample exam. IBM's DB2 Universal Database Version 7.1 for OS/390 delivers unparalleled performance, scalability, and reliability in today's enterprise e-business environments! Now, there's a complete, authoritative guide to deploying, managing, and developing applications with DB2 UDB V7.1 in both OS/390 and z/OS environments-and preparing for IBM's updated DB2 UDB V7.1 for OS/390 certification exam! Direct from IBM, this comprehensive day-to-day reference for running DB2 UDB in OS/390 and z/OS environments is also the only book with the in-depth knowledge professionals need in order to pass IBM's latest DB2 for OS/390DBA certification exam. Full of expert tips, techniques, and guidelines, it covers virtually every aspect of working with DB2 UDB in enterprise server: administration, connectivity, development, and much more. IBM Gold Consultants Richard Yevich and Susan Lawson present start-to-finish coverage of DB2's latest and most powerful enhancements, tools, and utilities, showing how to make the most of DB2 running on both OS/390 and next-generation z/OS platforms. Coverage includes: An overview of the DB2 UDB product family DB2 in OS/390 and z/OS environments: address spaces, attachments, interfaces, commands, and utilities Comprehensive security coverage, including access controls and auditing techniques SQL in depth: DB2 data structures, database objects, basic database design, and advanced coding DB2 UDB administration: maintaining data, backup/recovery, and more Performance monitoring and optimization: access paths, indexes, parallelism, buffer pool tuning, and subsystem tuning Data sharing: architecture and implementation in a Parallel Sysplex environment Detailed application d...